Two copper(II) compounds derived from tetrazole carboxylates for chemodynamic therapy against hepatocellular carcinoma cells - Shi, Xinya; Gu, Yulan; Wan, Chuandan; Jiang, Xin; Shen, Lei; Tan, Litao; Zhong, Yujie; Zou, Dengfeng (Frontiers in Chemistry, 2022)
Two Cu(II) compounds based on tetrazole-carboxylate ligands, [Cu(phtza)2(H2O)2]∙3H2O (1) and [Cu(atzipa)2]∙2H2O (2) (phtza = 2,2'-(5,5'-(1,3-phenylene)bis(2H-tetrazole-5,2-diyl))diacetate, atzipa = 3-(5-amino-1H-tetrazol-1-yl)isopropanoic anion), were designed and synthesized by hydrothermal reactions. The X-ray diffraction results show that the two compounds show two-dimensional (2D) layer structures. Nanoprecipitation with 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(polyethylene glycol)-2000] (DSPE-PEG-2000) contributes to the formation of the nanoparticles (NPs) with excellent water dispersity. In vitro study indicates that the two NPs exert considerable cytotoxicity toward human hepatocellular carcinoma cells (HepG2 and Huh7) with low half-maximal inhibitory concentration (IC50). However, the cytotoxicity of such NPs is negligible in normal cells (HL-7702). The cytotoxicity of these NPs was also investigated by the flow cytometry and Calcein-AM/PI (live/dead) co-stained experiments. The results promise the great potential of these NPs for chemodynamic therapy against cancer cells.